The determinant of safety management practices on safety behavior among medical devices manufacturing in Malaysia - Nazathul Nisha, Azahar (2022)
One of the main challenges in many organizations is workplace safety. This is due to the fact that workplace accidents and injuries may have both financial and non-financial consequences for the firm. Such neglect is unfortunate because Malaysia is one of several countries in the world where accidents and injuries occur frequently. A survey of 151 medical device manufacturing employees was conducted. Information on workplace safety behaviors and safety dimensions was collected using self-reported assessments. The proposed relationships were established using a structural model analysis using Statistical Package for the Social Sciences (SPSS). The current study discovered a substantial that influence safety behavior and six aspects of safety management practices (management commitment, safety training, worker involvement, safety communication and feedback, safety rules and procedures, and safety promotion policies). There is discussion of the implications for managers and practitioners. Respondents to this study included 151 Mediquip Sdn. Bhd. industrial operators in the state of Perlis. The study was conducted using SPSS 26.0. and various types of analysis. Regression analysis and ANOVA testing results generally support the existence of a positive relationship between safety management practices and safety behavior in the manufacturing of medical devices. Overall, this thesis will provide a comprehensive perspective on the topic of safety management practices on safety behaviour among medical devices manufacturing in Malaysia.